Survivors : the night the Titanic sank. - Jenner, Caryn (London : Dorling Kindersley Pub, 2001)
Details the parts and inner lives of trees and all the organisms that live within them.
Includes index.
Keywords: Readers -- Shipwrecks; Shipwrecks -- North Atlantic Ocean -- History -- 20th century -- Juvenile literature; Titanic (Ship) -- Juvenile literature